Myślistwo i religia. O religioznawczej ocenie praktyk łowieckich w perspektywie animal studies - Mitek‑Dziemba, Alina (Zoophilologica. Polish Journal of Animal Studies, 2018)
The main aim of the article is to consider the presence and function of religion (in most cases, the Christian religion) in the broadly conceived hunting practices at the turn of the 21st century, as well as the presence of religious motivation and ideological commitment in the hunters’ community from the perspective of religious studies inspired by the empirical research into the human-animal relationship (known as animal studies). The hunting narrative is shown, on the one hand, as eagerly seeking legitimacy and support from institutional religion (evidenced by the patron saints of hunting, the hunting ceremonial that has close parallels in the church ceremonial, and the argument in favour of “ecological balance” and “nature management” based on theological sources) and, on the other hand, as disguising an unethical and religiously unacceptable element of the arbitrary taking of life and inflicting pain without a shadow of empathy or without respecting the right to existence of what is a vulnerable being, even more so because it is devoid of human tools and rationality. The author’s examination of the issues leads to the discussion of the hunters’ religious mythologizing of their own status which draws on the ancient origin of hunting practices in prehistoric times: a period when the human-animal relationship was not yet marked by dualistic division and ontological asymmetry. The paper ultimately aims at the analysis of the way hunting is presented in religious studies research, of the difference between the implications of hunting activities for the human-animal relationship in premodern tribal communities (which practised subsistence hunting) and contemporary industrialized ones, and of the possibility of granting religious subjecthood to animals which stems from the return to the non-dichotomous, relational and dynamic view of the world typical of hunter-gatherers’ times.